LEGAL PROTECTION FOR VICTIMS OF PERSECUTION: AN ANALYSIS OF POSITIVE CRIMINAL LAW AND ISLAMC CRIMINAL LAW IN BATU BARA REGENCY - Ms, Purnama Wahyuni; Suparmin, Sudirman (Jurnal Ilmiah Advokasi, 2025)
Legal protection for crime victims is an endless problem in people's lives. Enforcement of legal protection for victims of persecution is an important aspect of the criminal justice system, in order to ensure justice and provide a sense of security.  This study discusses the enforcement of legal protection for victims of persecution, a review of Islamc criminal law and positive law, a case study of Batu Bara district, using the type of empirical legal research, conducting direct observations to the Women's Empowerment and Child Protection Office in Batu Bara Regency and the Batu Bara Police. The data source uses primary data with interviews, literature studies in the form of books, laws and criminal codes, which are analyzed into scientific papers. This study aims to analyze the obstacles faced in the legal protection process, including the inability of victims to access legal services, the less optimal role of law enforcement officials, and the lack of socialization of victims' rights. The results of the study show that although the victim protection law and then the Batu Bara Regency Regional Regulation exist, its implementation has not been maximized. Keywords: Law Enforcement, Victims, Abuse, Islam Criminal Law.